Exact welfare measurement of customs unions formation in the Caribbean Community: an hicksian alternative - Nicholls, Shelton M.A. (ISER MonaJA, 1993)
Attempts to measure the static welfare gains or losses which have resulted from the formation of CARICOM using Hicksian notions.